Management of Arabic Teacher’s Competency Improvement in Ma’had Abdurrahman Bin Auf Malang - Dewi Nur Diana; Moh. Iqbal Anshori; Nur Kholid (Shaut al Arabiyyah, 2022)
This research aimed to find out the management of Arabic teacher’s competency improvement in Ma’had Abdurrahman Bin Auf Malang. This research used a qualitative approach with the type of research is descriptive analysis. Planning to improve the competence of Arabic teachers is carried out by the head of the institution. The basis of planning competency improvement activities is the result of supervise of the head of the institution and evaluation of teachers by students through SIAKAD. Teaching competency improvement activities in this institution are "up grading" activities and training in the form of non-training organized by outside the institution. Some notes in the evaluation of the implementation of teaching competency improvement activities in this institution are 1) the basis of planning competency improvement activities is only two, namely the results of the supervision of the head of the institution and the teaching evaluation conducted by learners through SIAKAD, 2) competency improvement activities organized by the internal parties of the institution are only carried out once a year, 3) Not all teachers participate in competency improvement activities organized by outside the institution and that makes there is inequality and unevenness of competence owned by teachers in the institution.